Assessment of waste anesthetic gas concentrations in the operating theaters and DNA damage in exposed female nurse anesthetists - Thitiworn Choosong; Jatuporn Pakpirom (Clinical Epidemiology and Global Health)
Background: Personnel that work in operation theaters are at risk of exposure to waste anesthetic gases (WAGs) that can cause deoxyribonucleic acid (DNA) damage. To assess the potential impacts of single strand break levels of nurse anesthetists, WAGs levels, and other factors were investigated. Methods: Non-smoker nurse anesthetists (exposure group) and registered nurses (control group) that have never worked in operating theaters (OT) were matched by age. The WAG concentrations in OT were measured via a direct reading instrument. A blood sample of 2 mL from each volunteer nurse was used to determine the single strand break of DNA damage by comet assay; between July 2014 and January 2016. Results: In total 77 nurses participated in this study. Even if the average 8-h TWA of the WAG concentrations were low, N2O peaked at 951 ppm and sevoflurane peaked at 88.3 ppm during the induction phrase of pediatric patients. Multivariate analysis showed that ln (% of DNA) in the tail and ln (tail moment) were positively, significantly associated with N2O and cancer in family history, while ln (tail length) was not. However, dietary consumption of fish, meat and cruciferous vegetable had influence on DNA damage and shift work should not be neglected. Conclusion: Nurse anesthetists were potentially exposed to very high WAG concentrations; especially in pediatric cases. There were multi-factors associated with DNA damage score. To decrease the DNA damage score, lifestyle and dietary consumption should be of more concern.